Effect of ghrelin on the expression of Bcl-2 and Bax mRNA in in vitro maturation ovine oocytes - BAI, RUI-XIA; ZHAO, PENG -WEI; CAO, GUI-FANG (The Indian Journal of Animal Sciences, 2013)
The relationship between ghrelin and the expression of Bcl-2 and Bax was investigated. The result showed that ghrelin can regulate the expression of Bcl-2 and Bax. And ghrelin can promote ovine oocytes maturation in vitro. This maybe a good pathway to promote the animal production.